KEPERCAYAAN KONSUMEN DALAM MEMEDIASI PERSONAL SELLING DAN DAYA TANGGAP PT. ARKA KELOLA KONSULTINDO TERHADAP KEPUTUSAN PEMBELIAN ASURANSI KENDARAAN BERMOTOR - Kartika Maharani; Agus Sudigdo (ITB AAS Indonesia Surakarta, 2024)
In order to prove the influence of personal selling and company’s responsiveness that makes purchasing decisions with consumer trust as a mediating variable, research was conducted. This research was conducted at PT. Arka Kelola Konsultindo by taking 67 samples which is calculated by using the Slovin formula from a total population of 206 consumers who buy motor vehicle insurance in 2022 through PT. Arka Kelola Konsultindo, with a 10% margin of error. The research was conducted quantitatively and used WarpPLS 8.0 analysis with hypothesis testing using the t-test and sig 0.05. The research found that personal selling, responsiveness directly had a positive and significant effect on consumer trust, consumer trust had a positive and significant effect on purchasing decisions. Meanwhile, personal selling, responsiveness indirectly has a positive and significant effect on purchasing decisions through consumer trust.).